IMMU-07. Interim analysis of the HIT-HGG Rez Immunvac study - Dendritic cell vaccination with partial Treg depletion and double checkpoint blockade in children with relapsed high-grade gliomas. (3rd June 2022) - Eyrich, Matthias; Krauss, Jürgen; Ghaffari, Maryam; Caruana, Ignazio; Rachor, Johannes; Monoranu, Camelia-Maria; Bison, Brigitte; Rückriegel, Stefan; Wölfl, Matthias; Miller, Elisabeth; Schlegel, Paul-Gerhardt; Kramm, Christof
Abstract: Relapses of high-grade gliomas show an aggressive course and survival 6 months after (sub-)total re-resection was only 62% in former HIT-HGG trials. Immunotherapy by induction of tumor-specific T cells through active immunization might help to control glioma regrowth. In the HIT-HGG-Rez Immunovac trial (Eudra-CT 2013-000419-26) we investigate whether a therapeutic vaccine (autologous dendritic cells loaded with tumor lysate, DCV) combined with Treg -depletion and double checkpoint-inhibition (CI, anti-PD-1/anti-CTLA4) is able to increase the number of patients alive 6 months after relapse. Here, we report interim results after 50% of the intended patients (n=25) have been recruited. 13 children and adolescents (mean age 12.7±4.0 y) with relapsed glioblastomas were screened for the trial so far. Three patients were screening failures, 10 patients received study treatment. Of these, 2 patients are currently vaccinated, so that 8 patients were evaluable for this interim analysis. 5 SAEs have been reported so far, none of them was limiting. 4 patients with gross total or subtotal resection at time of relapse had an overall survival (OS) of 13.2±4.0 months and a 6-month survival rate of 100%, which compares favourably to historical controls. 4 partially resected patients survived only 5.1±1.3 months and 6-months OS was 25%. Treg -depletion lead to a reduction of CD4+CD127-CD25+ T-cells of 45%, the majority of patients exhibited a tumor-specific T-cell response. We conclude that DCV in combination with partial Treg -depletion and CI is feasible, safe, and related with immunological responses. Double CI was not associated with unexpected toxicities. In (sub-)totally resected patients, immunotherapy seems to confer a survival advantage. For the completion of the trial we aim to include more patients with (sub-)totally resectable tumors to gain more insight into the nature and duration of the induced immune response. This trial is supported by Bristol Myers-Squibb (CA209-7JA).